Nature’s Own Intellectual Creation: Copyright in Creative Expressions of Bioart - Härkönen Heidi; Ballardini Rosa Maria; Pietarinen Heidi; Sarantou Melanie (Nuart journal, 2025)
Bioart is a form of contemporary art, where non-human agents, that is, forces of nature contribute to the creative process. Correspondingly, the aim of copyright law is to protect artistic works, however according to the prevailing understanding only human-created expressions can be protected. From the perspective of European Union copyright law, this multidisciplinary article investigates whether bioart can be protected by copyright. As methods, the article combines a narrative research approach to the doctrinal study of law. The article finds that doctrinally, it is possible for bioart to merit copyright protection. However, the scenario puts forth remarkable challenges and obstacles.